2005
DOI: 10.1038/nature03345
|View full text |Cite
|
Sign up to set email alerts
|

Induction of photosensitivity by heterologous expression of melanopsin

Abstract: Melanopsin has been proposed to be the photopigment of the intrinsically photosensitive retinal ganglion cells (ipRGCs); these photoreceptors of the mammalian eye drive circadian and pupillary adjustments through direct projections to the brain. Their action spectrum (lambda(max) approximately 480 nm) implicates an opsin and melanopsin is the only opsin known to exist in these cells. Melanopsin is required for ipRGC photosensitivity and for behavioural photoresponses that survive disrupted rod and cone functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
354
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(389 citation statements)
references
References 33 publications
24
354
0
11
Order By: Relevance
“…The rhabdomeric photoreceptor cells may have transformed into ganglion cells expressing melanopsin, acquiring a new role in light detection and signal transduction [49]. First described in Xenopus, melanopsin is now known to confer photosensitivity on non-photosensitive cells types [50,51]. It has been hypothesized that melanopsin sets the circadian clock through non-ocular light detection [52], and is also expressed in sea urchins [30].…”
Section: Discussionmentioning
confidence: 99%
“…The rhabdomeric photoreceptor cells may have transformed into ganglion cells expressing melanopsin, acquiring a new role in light detection and signal transduction [49]. First described in Xenopus, melanopsin is now known to confer photosensitivity on non-photosensitive cells types [50,51]. It has been hypothesized that melanopsin sets the circadian clock through non-ocular light detection [52], and is also expressed in sea urchins [30].…”
Section: Discussionmentioning
confidence: 99%
“…The cascade in the ipRGCs is initiated through a receptor, melanopsin, which has greater sequence and biophysical similarities to the Drosophila rhodopsins [12][13][14][15][16][17][18] than the light receptors in rods and cones. Furthermore, pharmacological and electrophysiological studies suggest that the ipRGC cascade functions through a PLC and opening of channels that display features reminiscent of TRP channels [19][20][21]. Although, most of the specific signaling proteins in the ipRGCs remain to be identified, it appears that the Drosophila and mammalian ipRGC phototransduction cascades share common origins.…”
Section: Overview and Relationship Of Drosophila To Mammalian Phototrmentioning
confidence: 99%
“…higher similarities in sequence and biophysical properties to fly rhodopsins than the light receptors in rods and cones [10][11][12][13][14][15][16]. Some studies have demonstrated that ipRGC cascade functions through the activation of PLC and the opening of channels, which displays the features of TRP channels [10,17,18].…”
Section: Special Topicmentioning
confidence: 99%
“…Some studies have demonstrated that ipRGC cascade functions through the activation of PLC and the opening of channels, which displays the features of TRP channels [10,17,18].…”
Section: Special Topicmentioning
confidence: 99%